Genetics why were are who we are - Jackson, Tom (New York, NY Cavendish Square Publishing, 2018)
This book explores how genetics trace our understanding of heredity, from the discovery of inheritance to modern day, as scientists seek to manipulate genes to control the blueprints of life. Topics in this book include genetically modified food, epigenetics, stem cells, and xenobiology.--Provided by publisher.
Keywords: Genetics -- Juvenile literature; Genes -- Juvenile literature; DNA -- Juvenile literature